THE INFLUENCE OF SEED COATING PLUS BIOLOGICAL AGENTS IN INCREASING THE GROWTH AND YIELDS OF RICE WHICH CONTAMINATED WITH PHATOGEN BLAST - nortin .; Tantri palupi; Fadjar rianto (Fakultas Pertanian Universitas Tanjungpura, 2019)
Seed coating is a way to improve seed quality. The biological agent in coating formulas will improve the quality of contaminated seeds by blast patogen. The purpose of this study was to evaluate seed coatings-using biological agents to increase the growth and yield of blast infected seed rice in the green house. The study was conducted from December 04, 2018 to March 29, 2019 in the experimental garden of the Faculty of Agriculture, Tanjungpura University. This study used a completely randomized design method (CRD) consisting of 8 treatment with 4 replication and each treatment consisted of 3 samples. The coating treatment was added by philosphere bacteria isolate SP21, SP31, RP21, TP12, TP11, positive and negative control, fungicide. Variables observed such as plant height, maximum number of tiller , number of productive tiller, panicle length, grain weight per clump, percentage of grain fertile per panicle, weight 1000 dry seeds, environmental condition. The results showed that seed coating plus biological agents especially TP11 isolat can increasing the growth and yield of rice plants in green houses. It showed a significant effect on all observed variables except panicle length observation. Keywords: Coating, philosphere Bacteria, Biological Agents.